1979
DOI: 10.1002/cpt1979265611
|View full text |Cite
|
Sign up to set email alerts
|

Sulfinpyrazone kinetics after intravenous and oral administration

Abstract: Sulfinpyrazone kinetics has been investigated after intravenous and oral doses. They may be described by a 3-compartment open model. In the body about half the drug is in the plasma or in interstitial fluids, which equilibrated with plasma. Most of the rest is in an extravascular compartment, from which it easily diffuses back to the plasma. About 3% of the dose is still in the body after 24 hr and is located mainly in a deep compartment. After oral administration, sulfinpyrazone is quickly absorbed, largely f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

1981
1981
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 3 publications
2
7
1
Order By: Relevance
“…Shorter half-lives, 2.2 and 2.7 h, were found in two normal males given radiolabelled sulphinpyrazone by Dieterle et al (1975). The estimated AUCs were also comparable with the data of Lecaillon et al (1979) who found 89.2 + 23.0 ug ml-1 h for a 200 mg oral dose and 204.3 + 113 ,ug ml-' h for 400 mg. The ratio of the AUCs at the two doses was overall 2.4 (c.f.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Shorter half-lives, 2.2 and 2.7 h, were found in two normal males given radiolabelled sulphinpyrazone by Dieterle et al (1975). The estimated AUCs were also comparable with the data of Lecaillon et al (1979) who found 89.2 + 23.0 ug ml-1 h for a 200 mg oral dose and 204.3 + 113 ,ug ml-' h for 400 mg. The ratio of the AUCs at the two doses was overall 2.4 (c.f.…”
Section: Discussionsupporting
confidence: 83%
“…Shorter half-lives, 2.2 and 2.7 h, were found in two normal males given radiolabelled sulphinpyrazone by Dieterle et al (1975). The estimated AUCs were also comparable with the data of Lecaillon et al (1979) Lecaillon et al, 1979). However, the wider interindividual variation will be noted.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Both values are comparable to those of sulphinpyrazone. Lecaillon, Souppart, Schoeller, Humbert & Massias (1979) reported the plasma half-life of sulphinpyrazone to be about 3.8 h and the distribution volume to be 60 ml kg-'. Having these data in mind, the reductive pathway seems to be of major quantitative importance in the elimination of sulphinpyrazone during long-term therapy.…”
Section: Discussionmentioning
confidence: 99%